2020
DOI: 10.3390/nu12092538
|View full text |Cite
|
Sign up to set email alerts
|

Select Polyphenol-Rich Berry Consumption to Defer or Deter Diabetes and Diabetes-Related Complications

Abstract: Berries are considered “promising functional fruits” due to their distinct and ubiquitous therapeutic contents of anthocyanins, proanthocyanidins, phenolic acids, flavonoids, flavanols, alkaloids, polysaccharides, hydroxycinnamic, ellagic acid derivatives, and organic acids. These polyphenols are part of berries and the human diet, and evidence suggests that their intake is associated with a reduced risk or the reversal of metabolic pathophysiologies related to diabetes, obesity, oxidative stress, inflammation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 327 publications
(482 reference statements)
1
47
0
Order By: Relevance
“…During the current decade, clinical studies have dedicated to the health pro ts of berries. Especially, growing interest has been intense on the impact of berries and their natural ingredients in the human gut microbiota 45 , lipid metabolism 44 , diabetes and diabetes-related complications 46 , cardiovascular health 47 , and metabolic syndrome 48 .…”
Section: Discussionmentioning
confidence: 99%
“…During the current decade, clinical studies have dedicated to the health pro ts of berries. Especially, growing interest has been intense on the impact of berries and their natural ingredients in the human gut microbiota 45 , lipid metabolism 44 , diabetes and diabetes-related complications 46 , cardiovascular health 47 , and metabolic syndrome 48 .…”
Section: Discussionmentioning
confidence: 99%
“…Extensive research in humans who consume phytochemical-rich foods and beverages has revealed a wide range of potential health benefits against diabetes and related diseases; however, sufficient data to recommend specific phytochemical intake are lacking [ 83 , 84 , 85 , 86 ]. Among the wide varieties of phytochemicals, flavonoids are the largest and most evaluated group [ 87 ]. Flavonoids are a class of low-molecular-weight phenolic compounds widely distributed in plants [ 88 ].…”
Section: Phytochemicals and Glp-1mentioning
confidence: 99%
“…Polyphenols are naturally occurring compounds that possess antioxidant [ 18 , 19 , 20 ], anti-inflammatory [ 19 , 20 , 21 ], and anti-amyloidogenic [ 22 ] properties. As such, polyphenols have been hypothesized to prevent T2D [ 23 ] and AD [ 24 ]. Recently, we showed that IDE’s activity toward Aβ42 is sustained in the presence of resveratrol ( Figure 3 a) [ 25 ].…”
Section: Introductionmentioning
confidence: 99%